1999
DOI: 10.1007/s11916-999-0049-2
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary treatment of benign chronic pain syndrome in substance abusing patients

Abstract: This article presents a model for combined treatment of benign chronic pain and substance abuse. The combined treatment program illustrated draws resources from a comprehensive pain treatment center and an addictions program, which affiliated to better serve these challenging patients. Three illustrative cases are presented. Potentially divisive conceptual issues, such as lack of understanding of the biopsychosocial model of benign chronic pain, and the debate over the role of long-term opioid medication in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…37,48 Certain coping responses, such as task persistence, have been associated with better physical and psychological functioning among individuals with chronic pain, whereas other coping responses, such as pain-contingent resting and guarding, have been correlated with impaired function. 12,15,25,31,51 Cross-sectional and longitudinal studies have demonstrated that coping responses are associated with both short-and long-term adjustment to chronic pain.…”
mentioning
confidence: 99%
“…37,48 Certain coping responses, such as task persistence, have been associated with better physical and psychological functioning among individuals with chronic pain, whereas other coping responses, such as pain-contingent resting and guarding, have been correlated with impaired function. 12,15,25,31,51 Cross-sectional and longitudinal studies have demonstrated that coping responses are associated with both short-and long-term adjustment to chronic pain.…”
mentioning
confidence: 99%
“…74 Even with substanceabusing patients it is possible to develop a meaningful working relationship. 75 Opioid use can result in personality changes. 76 Staff meetings can include some of the following to avoid problems with bellicose patients.…”
Section: Patient Clinicianmentioning
confidence: 99%